2020
DOI: 10.1029/2020wr027931
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Coevolution of an Urban Human‐Water System Under Climate Change: Critical Role of Human Adaptive Actions

Abstract: The impacts of climate change and human activities are challenging water sustainability in many cities around the world. Advanced understanding of the future long‐term coevolution of coupled urban human‐water systems is of considerable interest in this context. This study uses a previously developed sociohydrologic model to explore the coevolutionary trajectories of Beijing City's human‐water system over the 2015–2099 period under possible climate changes. The effects of multiple human adaptive actions under a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…Many studies have shown that global warming intensifies the ecological impact of climate change and poses a nonnegligible Forests 2022, 13, 260 2 of 16 threat to human survival [14]. For example, under the dual effect of climate change and human activities, many cities around the world are facing water crises [15].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that global warming intensifies the ecological impact of climate change and poses a nonnegligible Forests 2022, 13, 260 2 of 16 threat to human survival [14]. For example, under the dual effect of climate change and human activities, many cities around the world are facing water crises [15].…”
Section: Introductionmentioning
confidence: 99%
“…There have been rapid global changes in land use and land management along with increasing water demands (Kumar et al, 2020). These changes have modified the hydrologic cycle at every scale resulting in the transformation of the landscape's hydrology around the world, significantly impacting societal development and ecosystem quality (Blair and Buytaert, 2015;Kumar et al, 2020;Li and Sivapalan, 2020). Sustainable water resource management is a critical component of food and energy production that is required to meet human demands (Roobavannan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in the field of sociohydrology include a range of objectives and goals, but are united in a multidimensional, interdisciplinary effort with the aim of establishing generalizable models that hold across time at a global scale (Pande and Sivapalan, 2017;Sanderson, 2018;Di Baldassarre et al, 2019). Modeling sociohydrological systems is inherently difficult because these systems operate at multiple scales, both spatial and temporal, and because of the uncertainty associated with predicting and assessing human activities along with climate change (Li and Sivapalan, 2020;Stephens et al, 2021). Moreover, as the world becomes increasingly globalized, leading to increasingly interconnected sociohydrological systems, there is a need to extend sociohydrology to the space-time domain in order to continue to be able to model and understand real world sociohydrological issues, which implies significant challenges (Pande and Sivapalan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Population size is an endogenous variable in the model, the dynamics of which are influenced by the drawdown of the groundwater table. B. Li and Sivapalan (2020) further explored the critical roles of human adaptive actions in the coevolution of groundwater and population. However, there remains a lack of understanding of the system dynamics under future environmental change and possible pathways that need to be invoked to adapt to the changing environment.…”
Section: Introductionmentioning
confidence: 99%